Metabolic effects of bezafibrate in mitochondrial disease - Hannah Steele; Aurora Gomez‐Duran; Angela Pyle; Sila Hopton; Jane Newman; Renae J Stefanetti; Sarah J Charman; Jehill D Parikh; Langping He; Carlo Viscomi; Djordje G Jakovljevic; Kieren G Hollingsworth; et al. (EMBO Molecular Medicine)
Abstract Mitochondrial disorders affect 1/5,000 and have no cure. Inducing mitochondrial biogenesis with bezafibrate improves mitochondrial function in animal models, but there are no comparable human studies. We performed an open‐label observational experimental medicine study of six patients with mitochondrial myopathy caused by the m.3243A>G MTTL1 mutation. Our primary aim was to determine the effects of bezafibrate on mitochondrial metabolism, whilst providing preliminary evidence of safety and efficacy using biomarkers. The participants received 600–1,200 mg bezafibrate daily for 12 weeks. There were no clinically significant adverse events, and liver function was not affected. We detected a reduction in the number of complex IV‐immunodeficient muscle fibres and improved cardiac function. However, this was accompanied by an increase in serum biomarkers of mitochondrial disease, including fibroblast growth factor 21 (FGF‐21), growth and differentiation factor 15 (GDF‐15), plus dysregulation of fatty acid and amino acid metabolism. Thus, although potentially beneficial in short term, inducing mitochondrial biogenesis with bezafibrate altered the metabolomic signature of mitochondrial disease, raising concerns about long‐term sequelae.